Modeling Seabed Response Under Ocean Waves: Research with Different Wave Properties - Wang Xuanyi (E3S Web of Conferences)
In order to study the seabed liquefaction under the wave effect and its key factors, this project will obtain the pore pressure in seabed soil, based on the Airy Wave theory and Biot’s theory. Referenced with the proper liquefaction criterion, the liquefaction depth is calculated easily under different wave heights and fixed soil mechanical parameters. The results show that the wave height has a significant influence on the seabed liquefaction depth. Increasing the wave height value can enhance the pore pressure development and the increase of liquefaction depth at the corresponding position in the seabed. According to the results output in this study, predicting and choosing the appropriate wave height values can be proposed as one of the methods to prevent seabed liquefaction.